1999
DOI: 10.1063/1.478200
|View full text |Cite
|
Sign up to set email alerts
|

Photofragment angular momentum distributions in the molecular frame: Determination and interpretation

Abstract: Photolysis of a molecule typically yields open-shell photofragments having angular momenta. A procedure is described for the measurement of the photofragment angular momentum distribution in terms of polarization parameters aq(k)(p) which are expressed in the molecular frame and which may be related to the transition dipole matrix elements. The index (p) indicates either a parallel transition (∥), a perpendicular transition (⊥), or a mixed transition (∥,⊥) having both parallel and perpendicular character. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
183
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(183 citation statements)
references
References 23 publications
0
183
0
Order By: Relevance
“…For most of the studies undertaken to date [6,7,9,10,12,14,15], the number of interacting molecular quantum states was limited to 2-3. In these cases, the relationship between the dynamical functions and the T-matrix amplitudes and phases is straightforward and the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y corresponding amplitudes and phases can be relatively easily determined from experimental data; see, for example, the review paper [25].…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For most of the studies undertaken to date [6,7,9,10,12,14,15], the number of interacting molecular quantum states was limited to 2-3. In these cases, the relationship between the dynamical functions and the T-matrix amplitudes and phases is straightforward and the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y corresponding amplitudes and phases can be relatively easily determined from experimental data; see, for example, the review paper [25].…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Several experimental studies have reported measurements of such orientation and alignment parameters (generically referred to hereafter as anisotropy parameters) for photodissociation of a variety of diatomic systems (see, for example, [6][7][8][9][10][11][12][13][14][15][16]), and results have been used to infer certain non-adiabatic crossing probabilities and phase shifts [10], as well as the shapes of molecular potential energy curves [17]. Theoretical analysis by Balint-Kurti and coworkers [2,3] pointed the way to the determination of all amplitudes and phases of T-matrix elements, and illustrated the connection to anisotropy parameters by using wavepacket propagation to compute the photodissociation dynamics of HF and HCl.…”
mentioning
confidence: 99%
“…1 have been fitted to the commonly used expression for one-photon dissociation and ͑2+1͒ REMPI detection processes: [63][64][65][66] …”
Section: B Angular Distributionsmentioning
confidence: 99%
“…In (a) and (b), filled circles represent data recorded in geometry (1), while open circles represent data recorded in geometry (2), as shown in figure 1. In (c), open circles represent data recorded in geometry (3), while filled circles represent data recorded in geometry (4). In all cases solid lines are the best simultaneous fit to all data, as described in the text.…”
Section: = 0 Photoproductsmentioning
confidence: 99%
“…This has been driven by the F o r P e e r R e v i e w O n l y 2 realization that these vector properties contain information not just on the magnitudes of different photofragment pathways, but also on their relative phases [3][4][5]. The vast majority of the experimental studies have investigated the orientation of the electronic angular momenta of the atomic products from the dissociation of diatomics, or in fewer cases, triatomics.…”
Section: Introductionmentioning
confidence: 99%